Analysis of Structural and Structural Changes in the Agrarian Sector of Our Country in Statistical Methods - Zakirova Umida Maxamadaminovna (Scientific Trends, 2025)
In this article describes the current state and dynamics of the country's agricultural sector, economic and statistical analysis of agricultural production in economic entities and promising areas.
Keywords: Agriculture, agricultural production, gross domestic product, gross regional product, agriculture, animal husbandry, structural changes, investments, regional economy, economic and statistical analysis, agrarian reform, socio-economic processes.